Ethnoscience as a Science Phenomenon in Science Learning to Increase Student Science Competency: A Literature Review - Kevin Jeremia Hutauruk; Nabilah Dwi Rahayu; Elis Kaiye; Alvina Meutia Anzalna; Dian Rahmawati; Farah Erika; Sukemi Sukemi (Postgraduate, University of Mataram, 2026)
Students' science competencies are challenged in science education. It is caused by the fact that science concepts are commonly presented abstractly and not contextually. This study aimed to systematically map the use of ethnoscience phenomena in science education and their contribution to enhancing students' science competencies. The method employed was a systematic literature review with a quantitative bibliometric approach, based on the PRISMA guidelines, utilizing published articles from Scopus, Google Scholar, Semantic Scholar, and SINTA (2019 – 2024). Forty-four articles met the inclusion criteria. The study results show that the ethnoscience phenomenon in science education can be classified into four main themes, namely traditional food processing, ecology and local environment, traditional technology and tools, and material culture and chemical processes, which are consistently related to three aspects of PISA science competency: explaining scientific phenomena, designing and evaluating investigations, and interpreting scientific data and evidence. It can be concluded that ethnoscience is an effective contextual bridge between science concepts - students' cultural experiences, and offering a novelty as thematic mapping of ethnoscience phenomena and theoretical mechanisms for improving science competency, which serves as a basis in science learning development based local culture in the future.